(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Data mining is another term for knowledge discovery in databases (KDD). It’s an interdisciplinary field that focuses on rooting meaningful knowledge from data in all sectors similar as health, education, and business. Currently, with the covid epidemic affecting everyone and rising coronavirus cases causing nursing home beds, oxygen, vaccines and individuals to be denied by hospitals, the health structure of the elderly is in the spotlight. There’s a wealth of information accessible in the medical world about these diseases. Data booby-trapping concepts may be used to prize meaningful styles from this type of material in order to prognosticate unborn followings. This study emphasizes on several mining approaches that will be applied in the therapy assiduity to achieve the stylish results.